The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1513/annalsats.202103-409oc
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Blood Eosinophil Variability in Asthma: A Real-Life Population Study

Abstract: Rationale: Blood eosinophil count predicts response to inhaled corticosteroids and specific biologic therapies in selected asthma patients. Despite this important role, fundamental aspects of eosinophil behavior in asthma have not been studied. ObjectivesTo investigate the behavior of blood eosinophils in a population comparing their distribution with the general population and studying their intra-individual variability over time in relation to hospital episodes (emergency department visits and hospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In addition, most of our patients would have been underestimated and/or overestimated with a single determination of AEC performed during a nadir or a peak in these cells, respectively (Figure 2B). Indeed, in recent studies performed in real-life settings on large cohorts of individuals, seasonal allergy was only one of several intrinsic and extrinsic factors causing intraindividual and interindividual variability in AEC in the general population as well as in the asthma population [11,24,25]. Therefore, it is conceivable that the MAEC assessment through four AEC determinations could be a more appropriate tool for managing patients with various eosinophilic conditions [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most of our patients would have been underestimated and/or overestimated with a single determination of AEC performed during a nadir or a peak in these cells, respectively (Figure 2B). Indeed, in recent studies performed in real-life settings on large cohorts of individuals, seasonal allergy was only one of several intrinsic and extrinsic factors causing intraindividual and interindividual variability in AEC in the general population as well as in the asthma population [11,24,25]. Therefore, it is conceivable that the MAEC assessment through four AEC determinations could be a more appropriate tool for managing patients with various eosinophilic conditions [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, this threshold is debated because an AEC of ≥150 cells/µL includes individuals with AEC in the normal range (300 to 500 cells/µL, [10]). In addition, recent studies performed on large cohorts indicated that the threshold of AEC identifying eosinophilic individuals is higher than ≥ 150 cells/µL in the general population (≥ 210 cells/µL [24] and ≥ 280 cells/µL [25]) and asthma patients (≥ 384 cells/µL [25]). Finally, it is unclear whether a single AEC can be used as a reliable marker for eosinophilic asthma [11,26].…”
Section: Introductionmentioning
confidence: 99%
“…The reason why high eosinophil is less likely the possibility of asthma and COPD compared with ACO, may be that the exacerbation frequency of ACO is higher than that of asthma or COPD alone ( 3 , 31 ). A large number of studies have shown that eosinophil is closely related to the exacerbation of COPD and asthma ( 32 34 ). Compared with patients without eosinophilia, those with eosinophilia (≥300 cells/μl) had a higher frequency of readmission for acute exacerbation of COPD (AECOPD) during the 1-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Jung et al 25 reported that a single eosinophil count may not suffice when managing eosinophilic asthma; several factors (including technical considerations) may influence the count. Toledo-Pons et al 26 reported that, compared with the absolute count, eosinophil variability was a better indicator of hospital episode risk. Because eosinophil stability may be problematic, other biomarkers that accurately reflect eosinophilic inflammatory status are needed.…”
Section: Discussionmentioning
confidence: 99%